Diagnostic and response assessment FDG PET‐CT in neurolymphomatosis. Issue 12 (28th October 2016) - Bruce, David; Eagleton, Helen; Subesinghe, Manil
Key Clinical Message: FDG PET‐CT is a useful imaging tool in the diagnosis and response assessment of neurolymphomatosis, especially in cases of otherwise unexplained neuropathy following conventional diagnostic work‐up including lumbar puncture, CT, and MRI. The use of a novel PET reconstruction algorithm improves image quality and lesion detection through increased signal‐to‐noise ratio. Abstract : FDG PET‐CT is a useful imaging tool in the diagnosis and response assessment of neurolymphomatosis, especially in cases of otherwise unexplained neuropathy following conventional diagnostic work‐up including lumbar puncture, CT, and MRI. The use of a novel PET reconstruction algorithm improves image quality and lesion detection through increased signal‐to‐noise ratio.